Short report and initial evaluation of the factor structure of the Lancaster and Northgate Trauma Scales (LANTS). (May 2021) - Wigham, Sarah; Hatton, Chris; Taylor, John L.
Abstract: Background: Research suggests exposure to adverse life events is elevated in people with intellectual disabilities. We developed the Lancaster and Northgate Trauma Scales (LANTS) to address the limited availability of screening questionnaires for people with intellectual disabilities affected by adverse traumatic experiences. Aims: The aims of this study were to (i) evaluate the factor structure of the self-report LANTS and (ii) assess compatibility with the International Classification of Diseases Eleventh Revision (ICD-11) criteria for complex PTSD. Methods and procedure: Ninety-eight people with mild to moderate intellectual disability (86 % men; mean age 41 years) completed the self-report LANTS. Exploratory factor analysis was undertaken using a polychoric correlation matrix, appropriate for the LANTS ordinal response options. Outcomes and results: Seven items including self-harm and anger were non-normal in distribution and excluded from the analysis; a four-factor structure was identified for the 22 remaining items. We make suggestions for correspondence of LANTS items to ICD-11 criteria for complex PTSD. Conclusions and implications: This is the first exploratory factor analysis of the LANTS. Items pertaining to anger and self-harm may be prone to response bias and development of these items using qualitative methods would be useful. The findings require replication with a larger group of people with intellectual disabilities, including more women.